2020
DOI: 10.3390/cancers12020256
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Functional Avidity of Tumor-Specific T Cell Receptors Using an Antigen-Presenting Tumor Cell Line Electroporated with Full-Length Tumor Antigen mRNA

Abstract: The functional avidity of T-cell receptor (TCR)-engineered T cells towards their cognate epitope plays a crucial role in successfully targeting and killing tumor cells expressing the tumor-associated antigen (TAA). When evaluating in vitro functional T-cell avidity, an important aspect that is often neglected is the antigen-presenting cell (APC) used in the assay. Cell-based models for antigen-presentation, such as tumor cell lines, represent a valid alternative to autologous APCs due to their availability, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…When we compared the reactivity of the DN4.99, PZP8A6 and DN4.2 TCR-JK cells against different doses of mLPA presented on K562-CD1c cells we found that, despite very similar levels of surface expression, the DN4.99 TCR exhibited a lower EC 50 (half-maximal effective concentration) than the other two TCRs, and the highest CD69 expression (Fig. 2e ), suggesting stronger functional avidity 14 , 15 upon antigen engagement.…”
Section: Resultsmentioning
confidence: 95%
“…When we compared the reactivity of the DN4.99, PZP8A6 and DN4.2 TCR-JK cells against different doses of mLPA presented on K562-CD1c cells we found that, despite very similar levels of surface expression, the DN4.99 TCR exhibited a lower EC 50 (half-maximal effective concentration) than the other two TCRs, and the highest CD69 expression (Fig. 2e ), suggesting stronger functional avidity 14 , 15 upon antigen engagement.…”
Section: Resultsmentioning
confidence: 95%
“…Fresh 5-10 x 10 6 IL-15 DCs were electroporated with WT1 mRNA in 250 µL OptiMEM (ThermoFisher Scientific) with an exponential decay pulse (300V, 150 µF) ( 7 ). U266, used as control antigen presenting cells (APCs), were treated identically but electroporated using a time constant pulse (300V, 8 ms) ( 23 ). WT1 mRNA transfection efficiency was determined 4 hours post electroporation by means of intracellular staining employing the eBioscience FoxP3/transcription factor intracellular staining buffer set (Invitrogen) and an anti-WT1 primary antibody (clone 6F-H2, Dako, Agilent, CA, US) as described previously ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the down-regulation of MHC-I on tumor cell surfaces helps tumor escape from the immunologic surveillance [ 68 ]. To improve the tumor’s immunogenicity, introducing mRNA encoding MHC-I and TAA [ 69 , 70 ] into tumor cells enabled the up-regulation of MHC-I. Thus, immune cells recognized tumor cells and pathogens rapidly, which improved the therapeutic efficacy of mRNA vaccines by enhancing viral/tumoral immunogenicity.…”
Section: Mechanisms Of Mrna Vaccine-mediated Immunotherapymentioning
confidence: 99%